Emergency preparedness and response plan in major cyanide handling companies - Tangavelu, Selva Kumar (1999)
Cyanide chemicals are highly toxic to human as well as environment. In Malaysia Cyanide chemicals are mainly used in electroplating industry. Among the main cyanide chemicals used are Potassium Cyanide (KCN). One of the world famous industrial accidents) Bhopal Disaster) is due to cyanide related chemical. In Malaysia so far we didn't experience any cyanide-related disaster yet but this doesn't mean that it will never happen especially when the number of electroplating companies in Malaysia are increasing. This research purpose is to assess the status of preparedness in handling cyanide emergency by cyanide handling companies. The companies selected for this research consists of two categories that are electroplating companies and cyanide chemical suppliers. The result of research clearly indicates that the cyanide chemical suppliers are less prepared to handle cyanide related emergency compare to electroplating companies. However most of the electroplating companies preparedness also not fully as per legal requirements or national and international guidelines or practises. Based on the research outcome a recommendation is made on the requirements of Emergency Preparedness and Response Plan in Cyanide handling companies. This recommendation expected to be very useful especially to the small scale electroplating or chemical supplying companies.